Patch Angioplasty or Primary Closure Following Carotid Endarterectomy for Symptomatic Carotid Artery Stenosis - Huizing, Eline (Surg J (N Y), 2018)
Objectives  Guidelines recommend routine patching to prevent restenosis following carotid endarterectomy, mainly based on studies performed many years ago with different perioperative care and medical treatment compared with current standards. Aim of the present study was to compare primary closure (PRC) versus patch closure (PAC) in a contemporary cohort of patients. Methods  Consecutive patients treated by carotid endarterectomy for symptomatic stenosis between January 2006 and April 2016 were retrospectively analyzed. Primary outcome was restenosis at 6 weeks and 1 year and occurrence of ipsilateral stroke. Secondary outcomes were mortality, complications, and reintervention rates. Results  Five hundred carotid artery endarterectomies were performed. Fifty-nine patients were excluded because eversion endarterectomy was performed or because they were asymptomatic. PRC was performed in 349 and PAC in 92 patients. Restenosis at 6 weeks was 6.0% in the PAC group versus 3.0% in the PRC group ( p  = 0.200). Restenosis at 1 year was 31.6 versus 14.1%, respectively ( p  = 0.104). No difference was found for stroke (3.4 vs 1.1%, p  = 0.319), death (1.1 vs 0.0%, p  = 0.584), or other complications (1.1 vs 0.0%, p  = 0.584), respectively. Conclusions  It remains unclear whether routine patching should be recommended for all patients. A strategy of selective patching compared with routine patching, based on internal carotid artery diameter and other patient characteristics, deserves further investigation.